The Role of Islamic Religious Education Teachers in Preventing Brain Rot Through Character Education at SMP Negeri 1 Manyaran - Muhamad Yamastio Sektiningtyas; Hafidz Hafidz (Electronic Journal of Education, Social Economics and Technology, 2025)
This study analyzes the role of Islamic Religious Education (PAI) teachers in preventing brain rot through character education at SMPN 1 Manyaran. Brain rot refers to the decline in critical thinking ability due to excessive consumption of superficial digital content, which impacts students' cognitive function and behavior. This research uses descriptive qualitative method, with interviews, observations, and literature studies as data sources. The results showed that PAI teachers play a significant role in instilling Islamic values, integrating character education in learning, and taking a personal approach in guiding students. This strategy is implemented through habituation of worship, teaching digital ethics, and strengthening self-control and discipline in the use of technology. However, the implementation of character education still faces challenges, such as students' high dependence on social media, lack of parental involvement, and teachers' low digital literacy. As a solution, the school developed a Ramadhan journal program to help students manage their time and reduce excessive digital consumption. This study confirms that collaboration between schools, parents and the government is crucial in improving the effectiveness of Islam-based character education in the digital era.